The Effect of Early Waking Habits on Elementary School Students’ Academic Achievement - Afifah; Sujana, Atep; Supriatna, Encep; Salim, Herli (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study is motivated by the importance of positive behavioral habits in supporting students’ academic achievement, particularly the habit of waking up early, which is associated with physical and mental readiness for learning. The purpose of this study is to analyze the relationship and effect of morning waking habits on students’ learning outcomes. This research employs a quantitative approach with a correlational design. The participants consisted of 50 students from a school in one of the districts in Serang Regency, selected using purposive sampling. Data were collected through a questionnaire to measure morning waking habits and documentation of students’ scores to obtain learning outcomes. Data analysis was conducted using IBM SPSS Statistics version 29, including Pearson correlation and simple linear regression analysis. The results indicate a positive and statistically significant relationship between morning waking habits and students’ learning outcomes, with a correlation coefficient of 0.62 (p < 0.05). Furthermore, regression analysis reveals that morning waking habits contribute 38% to students’ learning outcomes. These findings suggest that early waking habits can serve as a supporting factor in improving students’ academic performance, although it is not the only influencing factor